Resources for renewal : a participatory approach to the modernization of municipal organizations in Finland - Kalliola, Satu; Nakari, Risto (John Benjamins Publishing, 1999)
"In the 1990s, the public sector has experienced the same kind of productivity pressures as has the private sector in most of the western countries. In Finland, the state and the local government organs have pursued to meet these demands by cutting down their personnel costs and by applying various models of New Public Management. This book sheds light on the possibilities of solving the problems in public sector modernization by changing the modes of operations of work organizations. The results presented in the book are based on development expriences in Finnish municipalities, and cover a period of eight years (1991-1998).The participative approach is focused on the simultaneous development of the quality of working life and the productivity of services along the lines of Organizational Assessment. Thus, the book addresses some of the central issues within the debate on action research and on the modernization of the public services, such as “top-down” and “bottom-up” developments and the impact for the customers. A special feature in the book is a description of trade unions as actors in the development process and the role of trade union officials as developers."